Neuroprotective Mechanisms of Orientin against Hydrogen Peroxide-induced Oxidative Damage in SH-SY5Y Cells - Lim, Kit Ying; Sasmita, Andrew Octavian; Ling, Anna Pick Kiong; Koh, Rhun Yian; Voon, Kenny Gah Leong; Say, Yee How; Wong, Ying Pei (Journal of Biochemistry, Microbiology and Biotechnology, 2018)
Natural products or plant derivatives could be used to prevent or treat neurodegenerative diseases (ND). Oxidative stress has been highly implicated in the progression of ND;thus, this leads to the study on the effects of orientin in regulating Nrf2/Keap-1 redox signalling, PI3K/Akt survival and MAPK/ERK apoptosis pathways in the hydrogen peroxide (H2O2)-induced oxidative damage in SH-SY5Y cells. The cells were treated with half maximum non-toxic dose (½ MNTD) or maximum non-toxic dose (MNTD) of orientin and subsequently with H2O2. Cells were then subjected to the measurement of nitric oxide (NO), intracellular calcium (Ca2+), mitochondrial membrane potential (MMP) and annexin V/propidium iodide apoptosis assays. Regulation of the signalling pathways was analysed by Western blotting. Results showed that ½ MNTD of orientin reduced the NO levels. The intracellular Ca2+ level was also reduced by ½ MNTD and MNTD of orientin. The orientin treatment at ½ MNTD and MNTD restored the loss of MMP. Pre-treatment of orientin reduced the early and late apoptotic cells as well as necrotic cells. Orientin was found to up-regulate the Nrf2/Keap-1 and PI3K/Akt pathways whilst down-regulate the MAPK/ERK pathway. The findings from this study will be useful for the prevention of ND in the near future.